2. which equation is equivalent to the equation below?
5(n + 6) = 2(n-3) +4
a. 5n + 6 = 2n +1
b. 5n + 30 = 2n - 2
c. 5n +6=2n - 2
d. in + 30 = 2n +1​

Answers

The most obvious one i can think of would be

x = 13

Step-by-step explanation:

x + 8 = 21

x + 8-8 = 21-8

x = 13

Question:

Let p=x^2-2 .

Which equation is equivalent to in terms of p ?

p^2+18=9p or p^2+18 - 9p = 0

Step-by-step explanation:

Given

p=x^2-2 .

Required

Find the equation equivalent to (x^2-2)^2+18=9x^2-18

To get the equation equivalent to the given expression, we simply simplify (x^2-2)^2+18=9x^2-18 and solve in terms of p

(x^2-2)^2+18=9x^2-18

Factorize expression on the right hand side

(x^2-2)^2+18=9(x^2-2)

Substitute x^2 - 2 for p

(x^2-2)^2+18=9(x^2-2) becomes

p^2+18=9p

Hence, equation p^2+18=9p is equivalent to (x^2-2)^2+18=9x^2-18

Solving further to get the value of p

p^2+18=9p

Subtract 9p from both sides

p^2+18 - 9p = 9p - 9p

p^2+18 - 9p = 0

Rearrange

p^2 - 9p +18 = 0

Factorize

p^2 - 6p - 3p +18 = 0

p(p - 6) - 3(p -6) = 0

(p - 3)(p -6) = 0

p - 3 = 0 or p - 6 = 0

p = 3 or p = 6

Question 1:

For this case we must rewrite the following equation:

-3x + y = 5

If we add 3x to both sides of the equation we have:

y = 5 + 3x

Thus, we have that an equivalent expression is option C.

Option C

y = 5 + 3x

Question 2:

For this case we must solve the following equation:

-5x + 5 = -40

Subtracting 5 from both sides of the equation we have:

-5x = -40-5\\-5x = -45

Dividing between -5 on both sides of the equation we have:

x = \frac {-45} {- 5}\\x = 9

Option B

hello :

u(x)=x^5-x^4+x^2

u(x) = x² ( x^3 - x² +1)

what is v(x) ?

D

Step-by-step explanation:

given

(5x - 2)² + 35x - 14 = - 12 ← factor out 7 from 35x - 14

(5x - 2)² + 7(5x - 2) = - 12 ( add 12 to both sides )

(5x - 2)² + 7(x - 2) + 12 = 0 ← substitute m = 5x - 2, hence

m² + 7m + 12 = 0 → D

m² - 13m + 42 = 0

Step-by-step explanation:

Given m = x²

Then original equation

( x² - 5 )² - 3x² + 15 = -2

Now replace x² by m

( m - 5 )² - 3m + 15 = -2

Now considering ( m - 5 )² , we can open or expand the expression and later simplify. Therefore

( m - 5 )² = m² -10m + 25

Now put this in the above expression and simplify.

( m- 5 )² - 3m + 15 = -2 ,now becomes

(m² - 10m + 25) - 3m + 15 = -2

m² - 10m -3m + 25 + 15 + 2 = 0

m² - 13m + 42 = 0

m^2 - 13m + 38 = 0

Step-by-step explanation:

m = x^2\\(x^2-5)^2-3x^2+15=-2.

We can go simplify the equation by simplifying the first polynomial:

(x^2-5)^2 = x^4 - 10x^2+25

Then, we can substitute that in the original equation:

x^4 - 13x^2 + 38 = 0

Now, we can substitute m for every x^2.

Knowing that x^4 = x^2 * x^2, we can write this as m^2:

m^2 - 13m + 38 = 0

  b.  5n + 30 = 2n - 2

Step-by-step explanation:

The distributive property requires the outside factor be applied to every term inside parentheses. After eliminating parentheses using the distributive property, terms can be collected on the right.

  5(n +6) = 2(n -3) +4

  5n +5·6 = 2n +2(-3) +4

  5n + 30 = 2n -6 +4

  5n + 30 = 2n - 2 . . . . . matches choice B



Do you know the answer?

Other questions on the subject: Mathematics

the correct answer is you spend $55.78 more in a brand store that buy ing in a normal store.step-by-step explanation: brand = spend   $ 135.85 totalstore = spend $80.07 total...Read More
2 more answers
Mathematics, 21.06.2019, jhenifelix
answer is 8x+24area of vanessa's patio = length × width given, length = (3x² + 5x + 10) width = (x² - 3x - 1) area of vanessa's patio = (3x² + 5x + 10)(x² - 3x - 1) = 3x²(x² - 3x -...Read More
1 more answers
Mathematics, 21.06.2019, salazarx062
AttachedStep-by-step explanation:The equation given is ;y=√-x-3----------------------square left side to eliminate the root y²= -x-3graph  y²= -x-3 on a graph tool...Read More
1 more answers
Mathematics, 21.06.2019, jordan7626
Yes, that is the correct formula. to solve this problem given the number of years, plug in the number of years for t and plug the whole thing into the...Read More
1 more answers
Mathematics, 21.06.2019, jakails359
step-by-step explanation: here's what happens: 1) the graph of f   = x^2 is shifted 2 units to the right.2) the resulting graph is reflected in the x-axis, so that the parabol...Read More
1 more answers